Mapping the History of a Territory: Bon Pastor (Barcelona) – Social Remembrance and Heritage Project - Angosto, Salvador (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
The topic of the article are the complex stages of the formation of the Bon Pastor neighbourhood in Barcelona, and contemporary efforts to create the remembrance space system that would preserve the social memory and historical identity of the place. The author presents how the urban development plans for the district were transformed as a result of major changes in national politics, economy, and social policy, since the 1930s, through 60s and 70s, till today. The article describes the Bon Pastor Civic Memory project as an interesting example of a participatory action aimed at the preservation of local heritage. The implementation of the Civic Memory project was possible due to the neighbours’ initiative and their cooperation with cultural and academic institutions. The aim of this project is to mark certain points of the territory which possess historically and socially significant value, and to enhance them through public art, urban design and other implementations envisaged. The Association of residents of Bon Pastor (Barcelona) has been characterized, since 1974, for its combative and vindictive nature, at the same time as for its great capacity to launch solidarity initiatives and manage complicated processes to improve the living conditions of residents of the neighbourhood. After the struggles to obtain a health centre, the improvement of communications by metro and bus, and the constant improvement of public space, in recent years, the Association is co-managing with the Barcelona City Council, the radical transformation of the neighbourhood. The different phases for the remodelling of the neighbourhood, by replacing the so-called “cheap houses” with new buildings, with more spacious apartments and with better material conditions, is coming to an end and now, the possibility opens up, driven by the neighbours and the Museum of the History of the City (MUHBA) to have a metropolitan museographic space devoted to the presentation and study of the evolution of workers’ and popular housing in Barcelona.